Hykleriske Politikere, Demokrati og Mediedagsordenen - Lippert-Rasmussen, Kasper (Politik, 2014)
This article explores how accusations of hypocrisy function in political debates in the media. On the basis of a de nition of hypocrisy I argue that the strong media focus on hypocritical politicians: 1) gives an incen- tive for politicians to avoid subscribing to norms that are di cult or costly to comply with; 2) that often it is tied to the fallacy of inferring from the aws of hypocritical politicians to the claim that the norms they subscribe to are awed; 3) constitutes structural power that signi cantly a ects the possibility of putting certain, especially egalitarian, issues on the political agenda.